Latest MAGIC discoveries pushing redshift boundaries in VHE Astrophysics - Manganaro M; Becerra J; Nievas M; Sitarek J; Tavecchio F; Buson S; Dominis D; Dominguez A; Lindfors E; Mazin D; Moralejo A; Stamerra A; et al. (United Kingdom, 2022)
The search for detection of ?-rays from distant AGNs by Imaging Atmospheric Cherenkov Telescopes (IACTs) is challenging at high redshifts, not only because of lower flux due to the distance of the source, but also due to the consequent absorption of gamma-rays by the extragalactic background light (EBL). Before the MAGIC discoveries reported in this work, the farthest source ever detected in the VHE domain was the blazar PKS 1424+240, at z > 0.6. MAGIC, a system of two 17 m of diameter IACTs located in the Canary island of La Palma, has been able to go beyond that limit and push the boundaries for VHE detection to redshifts z similar to 1. The two sources detected and analyzed, the blazar QSO B0218+357 and the FSRQ PKS 1441+25 are located at redshift z = 0.944 and z = 0.939 respectively. QSO B0218+357 is also the first gravitational lensed blazar ever detected in VHE. The activity, triggered by Fermi-LAT in high energy ?-rays, was followed up by other instruments, such as the KVA telescope in the optical band and the Swift-XRT in X-rays. In the present work we show results on MAGIC analysis on QSO B0218+357 and PKS 1441+25 together with multiwavelength lightcurves. The collected dataset allowed us to test for the first time the present generation of EBL models at such distances.
XIV International Conference on Topics in Astroparticle and Underground Physics (TAUP 2015)